A case of ependymoma with unusual radiological presentation - Farzin, Mostafa; Teimouri, Javad; Alikhani, Mazdak (European Journal of Oncology and Environmental Health, 2018)
Ependymomas are glial tumors, usually seen as intra-axial lesions in MRI. Here we report a case of an extra-axial lesion, resected as a meningioma; but pathology report was a Myxopapillary Ependymoma. Further evaluation detected another lesion in distal part of spinal canal too. So it seems logic that extra-axial tumors be managed with more caution.